Diverticular disease of the jejunum - Ituño, Carlos; Bergalli, Luis (Cirugía del Uruguay, 1971)
The pathology of the diverticular disease of the jejunum is summarized and the author presents the case history of an 83 year old patient in which no such diagnosis had been made. The disease was discovered during an operation. A photograph of the specimen resected during the. operation is included.